Digital technologies and the teaching process - Nishio , Ana Lisa; Chung Marques Corrêa , Cynthia; Cassiano Nascimento , Jussara; Patricia Barboza de Souza , Márcia (Seven Editora, 2023)
This work is located in the context of the Covid-19 pandemic, during which time remote classes were instituted in public and private schools. We seek, through a qualitative research, to understand how the teachers of the cities of Juiz de Fora/MG and Petrópolis/RJ prepared their classes, adapting their pedagogical activities to the needs of the students, with the use of digital technologies. For data collection, we used the Form Google forms, sent to teachers from four municipalities - Juiz de Fora/MG, Magé/RJ, Petrópolis/RJ and Rio de Janeiro/RJ. Our studies were based on Moran (2008), Nóvoa (1995) and Tardif (2002). The results showed the need for adaptation by professionals and institutions to practices that allow students to use digital resources in the construction of knowledge; however, investments in public policies are needed for a better didactic use of network environments and appropriate use of digital technologies in educational institutions. DOI: https://doi.org/10.56238/tfisdwv1-052